Peroxisomal Leukoencephalopathy - Poll-The, Bwee Tien; Engelen, Marc (Seminars in Neurology, 2012)
Peroxisomal leukoencephalopathies include diseases belonging to the Zellweger spectrum and the rhizomelic chondrodysplasia punctata spectrum, as well as some single enzyme defects of peroxisomal β-oxidation. The authors present information on the clinical and diagnostic approach, and the characteristics of brain magnetic resonance imaging (MRI) in these diseases. MRIs of patients belonging to the Zellweger spectrum may show developmental anomalies and regressive changes consisting of abnormal cerebral white matter. Involvement of the central white matter of the cerebellar hemispheres is frequently seen. The leukoencephalopathy is progressive, with or without peripheral nerve involvement, in patients with a prolonged course of the disease. MRI characteristics in the severe phenotype of rhizomelic chondrodysplasia punctata include supratentorial white matter abnormalities, with a parietooccipital predominance. Demyelinative lesions are the hallmark of the cerebral form of X-linked adrenoleukodystrophy and may appear in a similar way in patients with adrenomyeloneuropathy progressing to a cerebral form. The diagnosis of a peroxisomal disorder can be determined by a battery of biochemical assays in blood and/or urine, and should be confirmed in cultured fibroblasts and DNA analysis. Treatment of the peroxisomal leukoencephalopathies is largely symptomatic, except for boys affected by the cerebral form of X-linked adrenoleukodystrophy in whom a bone marrow/hematopoietic stem cell transplant can be lifesaving, at least in the early stages of the disease.
Keywords: peroxisomal disorders; Zellweger spectrum disorders; rhizomelic chondrodysplasia punctata; x-linked adrenoleukodystrophy; leukodystrophy